Meta-analysis on the effect of dietary β-mannanase on intestinal integrity in broiler chickens - K. Poulsen; N. Mathlouthi; J. Bargen (Journal of Applied Poultry Research, 2023)
SUMMARY: The effect on intestinal health of using β-mannanase to degrade β-mannans, an intensely antinutritive fiber found in common broiler feed, was evaluated in a meta-analysis of lesion scoring data from 28 field trials completed in 13 countries from Europe (10) and the Middle East (3) between January 2013 and January 2020. The meta-analysis demonstrated that the addition of β-mannanase to commercial broiler diets reduced several conditions related to intestinal health and bird welfare. Notably, β-mannanase significantly reduced (P < 0.05) the prevalence of excessive cellular sloughing (CS) by 7.49 %-points, poor intestinal tone (IT) by 6.68%-points, excessive feed passage (FP) by 3.20%-points, abnormally thin intestines (TH) by 4.03%-points, litter eater (LE) or abnormal presence of litter in the gizzard by 1.99% and gizzard erosion (GIZ) by 8.45%-points. β-Mannanase also reduced (P < 0.05) the average lesion score for pododermatitis (BF). The general improvement of intestinal health was also evident in the intestinal integrity index (I2), which increased by 1.04 units in flocks fed diets with β-mannanase (P < 0.001). The analysis therefore suggests that β-mannan fibers from feed adversely affect a broad range of intestinal conditions, and consequently that the use of β-mannanase may improve intestinal health and welfare of commercial broiler flocks.